Alteração das características tradicionais da Igreja Assembléia de Deus: um estudo a partir da igreja do bairro Bom Retiro em São Paulo - Correa, Marina Aparecida Oliveira dos Santos (2006)
The present research is fruit of constant fidgets on as the church if it transforms front to the renewal of the environment and its people, as well as of your time. To modify a characteristic means that not to make different, before is necessary to renew positions and thoughts, without which the foreseen success is not reached. To study the church Assembly of God in the São Paulo's neighbor of the Bom Retiro, its traditional characteristics and socio-cultural factors, amongst others, made possible to understand as the societies human beings establish bonds from interests in common; and, in ours case, the search of new profiles of people appears a new image for the church. It also exists, a disruption with its philosopher-theological origins, appearing new forms, practical, distinct and divergent ways of if articulating with the faith, thus generating, a religious pluralism and new theology of understanding in its speeches. This alteration of characteristics comes of meeting with economic factors related to the welfare and the way of life based in the idea of the minimum state, or either, the auto determination of the people front to its longed for objectives. Therefore, we today have a church in transit, that follows the profiles objectified at definitive moments or situations, not necessarily in agreement with the daily payestablished rules, but breaching with these traditional standards and extending its continuity of works. Today, it is not more the people that adapts to the molds of the church, but is the church that adapts to the profiles of its people